TECHNOLOGY IN LANGUAGE TEACHING TODAY - Jack C. Richards (Universitas Katolik Indonesia Atma Jaya, 2015)
Technology is playing an increasing role in education world-wideand is having a growing impact on the design and delivery ofEnglish language programs. Todays’ language teachers areexpected to understand how to integrate technology into theirteaching as well as knowing how to help learners make use ofresources such as media and the internet to improve their learningof all four skills. As such technology offers both new challengesas well as new opportunities for both teachers and learners. Thisarticle surveys the role of technology in language teaching andexplores the opportunities it offers to teachers and learners tosupport new technology-mediated teaching and learning.Keywords: computer-assisted learning, flipped classroom,professional development, curriculum design,internet-based learning